ATSARU HARFATI AL-MUDARRIS ‘ALA RAGHBATI AL-THALABATI FII TA’ALLUMI AL-LUGHATI AL-‘ARABIYYATI - Isti Jayang Fitrah; Abdul Hakim; Salimul Jihad; Munirul Abidin; Baiq Laili Rahmawati (El-Tsaqafah : Jurnal Jurusan PBA, 2023)
This study aims to determine the effect of teacher’s professionalism on student’s interest in Arabic learning of class X MAN 1 Mataram for academic year 2020/2021. The population in this study were students of class X MAN 1 Mataram and the researcher took 45 students from the population to be used as samples in this study. The research approach used is quantitative research because the desired data is in the form of numbers. The researcher used three research instruments for collecting data namely questionnaires, documentation and observation. The data analysis used Pearson product moment correlation and simple regression with the help of SPSS 16.0 software. Based on the results of the correlation analysis, there was a positive and significant relationship with a correlation level of R=67% indicating a strong relationship between the two variables. And as for the results of the regression analysis, the researcher got the value of F arithmetic > F table 37.140> 4.06 with a significance level of 0.00 <0.05 so it can be concluded that there is an effect of teacher professionalism (X) on students' interest in learning Arabic (Y), with the contribution of the effect of teacher’s professionalism (X) on students' interest in learning (Y) is R Square = 45.8%. Therefore, the hypothesis which says "teacher’s professionalism effect on student’s interest in Arabic learning of class X MAN 1 Mataram for academic year 2020/2021 " is accepted